The effect of KOH concentration on setting time and compressive strength of fly ash-based geopolymer - Rahmiati, T. (Trans Tech Publications Ltd, 2014)
Geopolymer is produced from the alkali activation of materials rich in Si and Al such as fly ash. Sodium hydroxide (NaOH) with high concentration is normally used in geopolymerization. Limited research has been done with low concentration of alkali activator. This study confirms that KOH with low concentration affect the setting time and compressive strength of geopolymer in order to have good mechanical properties. Optimum result was observed at 4.5 M KOH. This result can be further developed to produce geopolymer with low alkaline activator for coating applications. Â© 2014 Trans Tech Publications, Switzerland.